Communications, contacts, ethics and the mysterious slow death of the contemporary police reporter - Philip Castle (Asia Pacific Network, 2007)
This article, based on interviews, research and the author’s personal experience in the media for more than 30 years as a police/crime reporter, former Head of Public Affairs for the Australian Federal Police and journalism lecturer, will examine the unique challenges and role of  reporting police/emergency/crime journalism—how it can work and how it can break down. It will particularly examine the mostly unequal relationships between journalists and official sources where the various emergency services, notably the police, trade on releasing selected information and avoid releasing information if it is unfavourable or inconvenient. It will cover the important aspects of sources, both official and unofficial, on and off-the-record agreements, anonymous sources, ethically and unethically obtained material and the all important overriding considerations of the law including criminal processes, defamation, sub judice, jurisdictional restrictions, pre-trial publicity and trial by the media. These stories can challenge even the most experienced journalist placing demands on almost all of their skills. If done properly, journalists can fulfil the paramount responsibility of informing the public on critical matters and maintaining the media’s role of being an effective Fourth Estate.